An estimation of the Banach-Mazur distance between the space of convergent sequences and a concrete model of a space of affine continuous functions - Villada Bedoya, Jeimer (Topological Methods in Nonlinear Analysis, 2025)
In this paper $c$ denotes the space of convergent sequences endowed with the supremum norm and $\mathcal{W}$ is the hyperplane of $c$ defined by $\mathcal{W}=\Big\{ (x(i))\in c: \lim\limits_{i→∞}({x(1)+x(2)})/{2}\Big\}$. We pose the problem of determining the Banach-Mazur distance $d(c,\mathcal{W})$ and present a method to estimate such distance from below together with tight bounds for $d(\mathcal{W},c)$.